KOMUNIKASI DALAM KELUARGA TRADISIONAL YANG MENGALAMI KONFLIK KARENA PILKADA DI KABUPATEN ALOR - Nandorari Saptenly Buling; Aloysius L.S. Soesilo (Jurnal Psikohumanika, 2021)
Electoral conflict that happens in Indonesia did not only occur in a large scale, but also in the smallest scale, such as inside the family. In Alor regency, electoral conflicts that occurs inside a family usually happens out of disagreements on the different political affiliations among the family members. Previous research did show how the hierarchy of authority inside traditional Indonesian family were formed, but it did not show how the hierarchy itself communicate and manage the conflict that risen inside that traditional family. This study tries to illustrate how the communications among family members occurs during and after the electoral conflict that happened on Alorese traditional family. This study uses descriptive-phenomenology approach, with emphasis on the participant’s subjective experiences. The results of this study shows that hierarchy of authority and the kinship within the traditional family does heavily affects the political affiliations, communication patterns and conflict management inside it. It also shows the important role of kinship on the reconciliation process between the family members after the conflict had concluded.